Primary follicular dendritic cell sarcoma of the kidney - a case report of a rare tumor with emphasis on diagnostic pitfalls - Tamás Pancsa; Borbála Dénes; Áron Somorácz; Dóra Kelemen; Ferenc Salamon; Fanni Sánta; Levente Kuthi (BMC, 2024)
Abstract Background Follicular dendritic cell sarcoma (FDCS) is a rare low-grade tumor of the lymph nodes, but roughly one-third of the cases emerge from extranodal sites, posing diagnostic challenges. Case presentation In this report, we present the case of a 59-year-old lady who complained of renal colic. During investigation, a kidney tumor was discovered. A radical nephrectomy was performed, and histological examination identified the tumor as a sarcomatoid renal cell carcinoma. The case was then referred to a genitourinary pathologist for further evaluation. The tumor cells exhibited positive staining for CD21, CD23, somatostatin receptor 2 A, and MDM2 expression. Additionally, MDM2 gene amplification was confirmed by the FISH study. Ultimately, the tumor was diagnosed as a primary renal FDCS. The patient was placed under active oncological surveillance and did not receive any further therapy. Remarkably, after 91 months of follow-up, she remains tumor-free. Conclusion This case represents a well-documented primary renal FDCS. Our aim in presenting this extremely rare tumor is to enhance awareness and highlight the importance of considering FDCS in the differential diagnosis.